Pengembangan Modul Sistematika Tumbuhan Tinggi Berbasis Guided Discovery untuk Mengembangkan Kemampuan Berpikir Kritis Mahasiswa Pendidikan Biologi - Anwari Adi Nugroho; Singgih Subiyantoro (Universitas Sebelas Maret, 2017)
This study aimed to know the characteristic of high plants systematics module based guided discovery indeveloping the ability to critical thinking for biology education students and to know the validity andpracticality of it. This research used modified Borg & Gall's method that was research and informationcollecting, planning, develop preliminary from of product, preliminary field testing, main product revision,main field testing, operational product revision. The product was high plants systematics module based guideddiscovery that a valid and practical. characteristic of this high plants systematics module based guided discoverywas contains activities with stimulation, problem statement, data collection, data processing, verification, andgeneralization. The result of preliminary field testing include learning module expert validation, module expertvalidation and learning materials expert validation indicated that the module was feasible and did not need anyrevision. The results of main field testing included practitioner and student test shows that the module is feasible(practical)